Avaliação da secagem convectiva de resíduos da indústria cervejeira - Pinto, Guilherme Henrique Alves (Universidade Federal de São Carlos, 2020)
Brazil is the third largest beer producer in the world, with an estimated production of 14.1 billion liters of the product for the year 2018, generating several co-products throughout the process, being brewer’s spent grain and spent yeast the main ones. The reuse of these materials is more interesting from the economic and logistical point of view in relation to the usual destination, however it is necessary to understand their drying to make their new destination viable. The present work aimed to evaluate the operational feasibility of reducing the humidity of both materials through convective drying, applying different dryers for each co-product. To malt bagasse drying was used a system consisting of a rotary pan with a capacity of 10 liters associated with a blower responsible for the hot air supply. It was evaluated how the drying kinetics, temperature profile, specifically the temperature on the inner surface, Tw, and the spent grain temperature, Ts, and the solids circulation intensity were affected by the dryer operational conditions, specifically the air temperature at the blower outlet, TaE, the spent grain mass added to the system, ms, and the pan rotation, Ωdrag. For this purpose, two different values were used for each parameter, TaE=67.7 and 101.2 °C, ms,0=1.0 and 1.5 kg, and Ωdrag=25.1 and 33.9 rpm. The drying tests were carried out until the dynamic equilibrium moisture content was reached. It was necessary 180 minutes of drying to achieve dynamic equilibrium with TaE = 101.2 °C and ms,0=1.0 kg, while for TaE=67.7 ° C and ms,0=1.5 kg were necessary 420 minutes of drying, being noticed a significant influence of TaE and ms,0 on the kinetics. By modifying Ωdrag maintaining TaE and ms, dynamic equilibrium was achieved at the same drying time, with no significant influence of Ωdrag on the process. The solids circulation, Ωs, presented a parabolic profile with a minimum value of approximately 16 rpm at the beginning and end of drying and a maximum value of approximately 27 rpm in the intermediate periods. As the dryer rotation remains constant throughout the operation, it was concluded that the bed properties modifications, mainly spent grain moisture, induced the profile observed for Ωs. Tests were carried out using the centrifugal method to relate the adhesion force between the dryer surface and the spent grain with its moisture content, being observed forces of greater intensity for the material in its original conditions and practically null forces with a completely dry material, behavior commonly observed in materials in which the capillarity effects predominate in surfaces contact. The temperature profile showed a behavior that could be divided into three distinct periods, a period corresponding to the beginning of drying, in which the dryer surface and spent grain were in thermal equilibrium, with Tw approximately equal to Ts, an intermediate period, in which Tw was greater than Ts, and a third period corresponding to the end of drying, in which Tw was lower than Ts. It was possible to conclude that the adhesion between the spent grain and the surface also caused this temperature behavior, especially in the first period, when the stronger contact between the phases by capillarity provided the thermal equilibrium. It was concluded that the spent grain adhesion to the dryer surface affected its operation, especially in the particles circulation and the temperature profile. In the spent yeast drying, a vibrofluidized bed dryer was used, fixing the vibrational conditions, A=0.015 m and f=500 rpm, and the paste feeding at 14 mL/min, varying the drying air temperature at 80 or 100 °C, the mass of glass spheres at 0.5 or 1.5 kg and the superficial velocity of the fluid at 1.5umf and 1.2umf to evaluate the effect of these parameters on product formation, material accumulation, fluid dynamics of the bed and product quality. Each drying test was conducted for 30 minutes, followed by 30 minutes with no paste feeding for the dry material detachment. There was a change in the fluid dynamics curve for different inert masses, with a reduction in the minimum fluidization velocity and in the pressure drop with a lower static bed height. For 1.5 kg of inert, 80 °C and 1.2 umf, no product formation was observed, unlike the other tests with different operational conditions, evidencing their influence on the production rate, the highest rate, 0.263 g/min of dry poder, was observed using na inert mass of 1.5 kg and air feeding at 1.2 umf and 100 °C. However, the production rates achieved were considerably small compared to the paste feed. At the end of drying, it was possible to observe a low detachment of material from the inert surface, maximum 0.532 g/min. Thus, most of the material fed into the dryer remained attached to the inert and chamber wall, indicating that the material detachment limited the operation. Drying was sufficient to reduce the moisture content, from 90.63% on a wet basis to a maximum of 8.12%. For each test, the product moisture content for 10 to 20 minutes of drying was higher than that obtained in the initial and final 10 minutes. It was not possible to obtain a clear relationship between the product’s cell viability and the operational conditions.
Evaluation of convective drying of brewing industry's wastes
Keywords: Secagem; Bagaço de malte; Levedura residual; Drageadeira; Leito vibrofluidizado; Drying; Brewer's spent grain; Brewer's spent yeast; Rotary pan; Vibrofluidized bed; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA